Type of Subtitling Strategies in Parker Movie - Wahyudi , I Made Panji Resa; Utami , Ni Made Verayanti; Hikmaharyanti , Putu Desi Anggerina (Institut Pariwisata dan Bisnis Internasional, 2024)
The writer conducted research on the translation strategy used in the subtitled film